(untitled) (Academia Journal of Medicine, 2026)
Postoperative pain following endodontic treatment remains a significant clinical concern influenced by irrigation techniques. This study aimed to evaluate and compare postoperative pain following different irrigation activation methods in single-visit endodontics. A total of 90 patients were divided into three groups based on the irrigation technique used: manual dynamic agitation, passive ultrasonic irrigation, and laser-activated irrigation, and pain was assessed at different time intervals using a numerical rating scale. The results demonstrated variations in postoperative pain among the groups, with advanced activation techniques showing better pain reduction compared to conventional methods. It can be concluded that irrigation activation techniques play a significant role in minimizing postoperative pain, and their appropriate selection can improve patient comfort and clinical outcomes. Advancement of Knowledge This study provides comparative clinical evidence on the effect of different irrigation activation techniques on postoperative pain following single-visit endodontic treatment. It demonstrates that advanced activation methods, such as passive ultrasonic irrigation and laser-activated irrigation, are more effective in reducing postoperative pain compared to conventional approaches.The findings highlight the role of improved irrigant penetration and reduced apical extrusion in minimizing periapical inflammation and patient discomfort. Additionally, this study emphasizes the importance of selecting appropriate irrigation techniques as a key factor in enhancing clinical outcomes and patient satisfaction in endodontic therapy.